Development and Application of a Simple “Easy To Operate” Propidium Monoazide-Crossing Priming Amplification on Detection of Viable and Viable But Non-culturable Cells of O157 Escherichia coli - Zhou, Wenqu; Wang, Kan; Hong, Wei; Bai, Caiying; Chen, Ling; Fu, Xin; Huang, Tengyi; Liu, Junyan (Frontiers in Microbiology, 2020)
O157 Escherichia coli is one of the most important foodborne pathogens causing disease even at low cellular numbers. Thus, the early and accurate detection of this pathogen is important. However, due to the formation of viable but non-culturable (VBNC) status, the golden standard culturing methodology fails to identify O157 E. coli once it enters VBNC status. Crossing priming amplification (CPA) is a novel, simple, easy-to-operate detection technology that amplifies DNA with high speed, efficiency, and specificity under isothermal conditions. The objective of this study was to firstly develop and apply a CPA assay with propidium monoazide (PMA) for the rapid detection of the foodborne E. coli O157:H7 in VBNC state. Five primers (2a/1s, 2a, 3a, 4s, and 5a) were specially designed for recognizing three targets, which were rfbE, stx1, and stx2, and evaluated for its effectiveness in detecting VBNC cell of E. coli O157:H7 with detection limits of pure VBNC culture at 103, 105, and 105 colony-forming units (CFUs)/ml for rfbE, stx1, and stx2, respectively, whereas those of food samples (frozen pastry and steamed bread) were 103, 105, and 105 CFUs/ml. The application of the PMA-CPA assay was successfully used on detecting E. coli O157:H7 in VBNC state from food samples. In conclusion, this is the first development of PMA-CPA assay on the detection of VBNC cell, which was found to be useful and a powerful tool for the rapid detection of E. coli O157:H7 in VBNC state. Undoubtedly, the PMA-CPA method can be of high value to the food industry owing to its various advantages such as speed, specificity, sensitivity, and cost-effectiveness.